Maidekost Website Improvement Recommendations Based on User Experience and USE Questionnaire Evaluation - Maricar, M. Azman; Edwar, Edwar; Simangunsong, Batara FS; Anisa, Aura Pirdaraya Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2023)
The troublesome search for temporary housing information is the background for the creation of the Maidekost platform. The Maidekost website has existed since its inception but has not been operational until now. This raises the assumption that there is a problem with usability. Maidekost has been evaluated from a usability perspective with interviews and the USE Questionnaire. The results of a high usability predicate and a feasibility percentage of 79.96% were obtained and several things needed to be fixed. The focus of this study aims to provide recommendations for improvement in the form of a prototype and these recommendations are tested again with the USE Questionnaire. The results obtained are an increase in the average usability of 0.11 but does not affect the usability predicate, which is still at the high predicate. In terms of the percentage of eligibility, there was an increase of 1.95%, so that it became 81.91% which was initially feasible to be very feasible to use. In other words, the recommendations given are able to increase usability and can be implemented.